A revolutionary crowd model: Implemented to contrast oscillating to consistent media influence on crowd behavior. (November 2017) - Ibrahim, Yasser; Hassan, Rasha
Since Le Bon introduced his profound theory about the crowd in 1895, the phenomenon has been investigated across a range of scientific disciplines. Nevertheless, the mystery of the popular mind seems so far unrevealed, especially with the emergence of unfamiliar crowd movements, such as Twitter revolutions, which are triggered by novel types of media and interpersonal communication. Such original collective behavior, along with the current turbulent sociopolitical global environment, has necessitated the development of explanatory contemporary models. This research introduces a new revolutionary crowd model with a unique set of internal and external factors that can fit the modern uprisings in order to enable the understanding of the conditions that could lead to or prohibit the formation of revolutionary crowds. The model is implemented to examine the effectiveness of oscillating intensified mass media on the crowd pattern and dynamics. Among several emergent behaviors, the model shows an insignificant impact of disrupted intensified media on the crowd, in contrast with consistent low-intensity media, the failure of contagion theory in sustaining a revolution without a persistent stimulus, and the refutation of current claims of the insignificancy of leaders' roles in igniting and maintaining modern crowds.